Microcredit in Viet Nam: Does it matter? - Haughton, Jonathon; Khandker, Shahidur R. (International Food Policy Research Institute, 2016)
With 7 million borrowers and US$5.4 billion in outstanding loans in 2012, the Viet Nam Bank for Social Policies (VBSP) is the largest single microcredit lender in the world. We measure the impact of VBSP lending and seek to answer the question of whether continued subsidies to the bank, which amount to about 2 percent of the value of its loans, are justified. VBSP grew particularly rapidly between 2004 and 2008, when its share of total loans in Viet Nam rose from 10 to 27 percent, and by 2008 an estimated two-fifths of its loans were ostensibly used for directly productive purposes. Using data from a panel of 1,846 rural households interviewed in 2004, 2006, and 2008 as part of the Viet Nam Household Living Standards Survey, we estimated the impact of VBSP lending on consumption and income per capita, as well as self-employment earnings. Both an intention-to-treat model with fixed effects, and a quantity-of-credit model with fixed effects and using instrumental variables, show significant or close to significant impacts of VBSP microloans on consumption and income, but our data do not have enough power to determine whether this mainly works via agricultural or nonagricultural self-employment income. Without VBSP, the rural poverty rate would have been 0.7 percentage points higher in 2008 than it actually was. The subsidy is likely justified, given the evidence and scale of the positive impact of VBSP loans on consumption spending and the concentration of benefits among poorer households in Viet Nam.